Expressão de genes imunológicos em camarões Litopenaeus vannamei desafiados experimentalmente com o vírus da mionecrose infecciosa e tratados com dsRNA produzidas in vivo - Freitas, Juliana Oliveira de (2020)
Shrimp farming is one of the fastest growing aquaculture activities in the world and the Pacific white shrimp (Litopenaeus vannamei) is the most widely cultivated species. Although shrimp farming shows significant growth, the manifestation of diseases hinders its progress. The disease caused by the Infectious Myonecrosis Virus (IMNV) causes significant losses in Brazilian shrimp farming. Recent evidence has suggested that interference RNA (RNAi) could be a viable alternative to control viral diseases. The present work aimed to evaluate the dynamics of immunological gene expression in L. vannamei shrimp experimentally infected with IMNV and treated with dsRNA molecules produced in vivo by Bacillus subtilis JJBs3 containing the IMNV sequence of ORF1a. In a first experiment, the progress of the infection caused by two dilutions (1.02 x 104 and 1.02 x 103 copies / 100 μl) of an IMNV-infected tissue extract was monitored by quantifying viral copies by RT- qPCR and histopathological methods; IMNV and SPF (free from IMNV, WSSV and IHHNV) extracts were validated through experimental intramuscular injection infection lasting 22 days. Groups infected with IMNV extract showed survival curves with significant differences (p<0.05) in relation to the two control groups (saline solution and SPF tissue extract), as well as histopathological alterations. Significant differences (p<0.05) in viral load were observed in treatments III and IV between the 2nd and 6th day after infection, among three collection points, with average values of 1.33 x 102 to 1.59. x 107 viral copies, respectively. Expression of immunological genes (Sid-1, Dicer-2, Argonaut-2, proPO-1 and PPAE-1), was evaluated by qPCR, applying the 2-ΔCq method. In most cases expression reduction was observed. However, Sid-1 and Argonaut-2 showed expression increase in the treatment with the lowest viral dose. In the second experiment (25 days; six treatments; four sampling points), the effect of different doses (0.5, 1.0, 3.0 and 5.0 μg dsRNA per gram of shrimp), administered by intramuscular injection two days before the challenge, was monitored. Two control groups were used, in one of them the animals were injected with saline and SPF tissue extract (negative), and in the other, with saline and infected tissue extract (positive). Histopathological changes characteristic of IMN and significant differences (p<0.05) in viral load between the 2nd and 8th post-injection day were verified in cases where IMNV was applied. No differences were observed in the extent or expression of the genes analyzed throughout the experiment, suggesting that in the present conditions dsRNAs had no protective effect. Because this is a new model of dsRNA production, the techniques of use, purification, quantification as well as the delivery methods of these molecules need to be improved.